Epitaxial growth of thin TiO2 films on the Au covered Fe(100) surface. Issue 8 (11th April 2014) - Brambilla, A.; Calloni, A.; Berti, G.; Bussetti, G.; Duò, L.; Ciccacci, F.
<x xml:space="preserve">Abstract</x> In this work, we investigate the possibility of growing high‐quality TiO2 thin films on Fe(100) by intercalating a thin Au buffer layer. X‐ray Photoemission Spectroscopy and Low Energy Electron Diffraction are employed to investigate the electronic and structural properties of the TiO2/Au/Fe interfaces. We obtain crystalline rutile films with a reduced number of defects when compared to room temperature grown TiO2/Fe(100) samples but with some degree of interface mixing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>